ASSESSING THE RELATIONSHIP BETWEEN INTERNATIONAL MARKET AND AGRICULTURAL COMMODITY EXPORT PRICES: EVIDENCE FROM VIETNAMESE COFFEE - Đặng, Trung Tuyến (Trường Đại học Đà Lạt, 2023)
The paper used a cointegration test, the Granger causality test, and a vector autoregression (VAR) model to determine the relationship between the international coffee price on the spot market and the Vietnamese coffee export price from January 2004 to December 2017. The study found international coffee prices to have a significant effect on Vietnamese coffee export prices, but not vice versa. The two variables are not cointegrated with each other at the 99 percent confidence level, but the Granger causality test confirmed that the Vietnamese coffee export price is influenced by the international market price, while the international market price is not influenced by the Vietnamese coffee export price. The results from the VAR model also showed that the dependent variable is mainly impacted by two independent variables in lag 1 and other lags. Overall, the Vietnamese coffee export price did not have an effect on the international coffee spot market price. Therefore, the relationship between the international coffee price and the Vietnamese coffee export price is asymmetric. These results are in accordance with the actual situation since Vietnam is the largest exporter of robusta coffee in the world, but Vietnam is only a “small” country that has no market power in the international coffee market.